An outbreak of human Leishmania (Viannia) braziliensis infection - Francisco Oscar de Siqueira França; Ednaldo Lago; S Tada; Jackson M. L. Costa; Kyola C. Vale; Juliana Costa de Oliveira; M. A. Costa; Masami Osaki; Laura W. Cheever; Eduardo Martins Netto; A.C. Barreto; William D. Johnson; et al. (1991)
The occurence of acute cutaneous leishmaniasis among inhabitants of 10 farms within 10 Km of the hamlet of Corte de Pedra, Bahia, Brazil was studied prospectively from 1984-l989. A mean population of 1,056 inhabitants living in 146 houses were visited every 6 months and the number of sKin ulcers recorded. A leishmanin skin test survey was done people with suggestive skin scars or active disease in l984. The incidence of skin ulcers due to Leishmania (Viannia) brasiliensis (Vlb) reached 83/1,000 inhabitants but declined sharply in the subsequent 2 years. Retrospective data shows that leishamiasis is a sporadic endemic disease. Although the reasons for this epidemic are unclear some possible aetiological factors are discussed.